Development of an ultrafast low-energy electron diffraction setup - Gulde, Max (Springer Theses, Recognizing Outstanding Ph.D. Research, 2015)
This book presents an Ultrafast Low-Energy Electron Diffraction (ULEED) system that reveals ultrafast structural changes on the atomic scale.  The achievable temporal resolution in the low-energy regime is improved by several orders of magnitude and has enabled the the melting of a highly-sensitive, molecularly thin layer of a polymer crystal to be resolved for the first time.This new experimental approach permits time-resolved structural investigations of systems that were previously partially or totally inaccessible, including surfaces, interfaces and atomically thin films. It will be of fundamental importance for understanding the properties of nanomaterials so as to tailor their properties.